Primary prophylaxis for cryptococcal meningitis and impact on mortality in HIV: a systematic review and meta-analysis. (September 2013) - Ssekitoleko, Richard; Kamya, Moses R; Reingold, Arthur L
Aim: To determine the role of primary antifungal prophylaxis in the prevention of cryptococcal meningitis and all-cause mortality in advanced HIV infection.Materials & methods: This was a systematic review and meta-analysis of randomized trials and observational studies. Google Scholar™, PubMed and Embase databases were searched for relevant studies. Quality was assessed using different criteria, depending on study type. Publication bias was assessed and subgroup and sensitivity analyses were performed. When the results of the meta-analysis were homogeneous, the fixed-effects model was used; when the results of the meta-analysis were heterogenous, the random effects model was used.Results: Primary prophylaxis prevented cryptococcal meningitis but did not confer protection against overall mortality, although there was evidence of a reduction in cryptococcal-specific mortality in resource-limited settings.Conclusion: Primary antifungal prophylaxis should be recommended in patients with advanced HIV infection in resource-limited settings with a high incidence of cryptococcal meningitis.